INTEREST GROUPS AND AMERICAN FOREIGN POLICY: THE CASE OF AIPACâS ROLE IN IRAQ WAR - , KIKI MUTIARA NUGRAHENI, Drs. Dafri Agussalim, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research deals with interest groups and American foreign policy. The problem dealt within this research is to know the role of interest groups in American foreign policy. In order to know the role of interest groups In American foreign policy, this research takes the role of AIPAC in Iraq invasion as the case to be explored. In doing this study, this research applies library research which is conducted within American studies framework. It applies interdisciplinary which involves historical approach and political approach to give the clear understanding about the role of AIPAC in Bushâs policy war against terrorism which is invading Iraq on 2003. The research findings show that AIPAC has significant role in Iraq invasion. Through the exploration of political structure and history of United States, the research findings hoe AIPAC having chance to shape American foreign policy like Iraq invasion 2003 in many different ways such as lobbying elected representatives and members of the Executive branch, making campaign contribution, voting in election and molding public opinion. The significant role of AIPAC in Iraq invasion shows how the democratic system of United States leads to the tyranny of minority.